Vulnerability and resilience to cardiovascular and neuroendocrine effects of stress in adult rats with historical of chronic stress during adolescence - Duarte, Josiane O. [UNESP]; Planeta, Cleopatra S. [UNESP]; Crestani, Carlos C. [UNESP] (Elsevier, 2023)
Aims: This study investigated the influence of exposure to stress during adolescence in autonomic, cardiovascular, neuroendocrine and somatic changes evoked by chronic stress in adult rats. Main methods: Animals were subjected to a 10-days protocol of repeated restraint stress (RRS, habituating) or chronic variable stress (CVS, non-habituating) during adolescence, adulthood, or repeated exposure to either RRS or CVS in adolescence and adulthood (adolescence+adulthood group). The trials to measure autonomic, cardiovascular, neuroendocrine and somatic changes in all experimental groups were performed in adulthood. Key findings: CVS increased basal circulating corticosterone levels and caused adrenal hypertrophy in the adolescence+adulthood group, an effect not identified in animals subjected to this stressor only in adulthood or adolescence. CVS also caused a sympathetically-mediated resting tachycardia in the adulthood group. This effect of CVS was not identified in the adolescence+adulthood group once the increased cardiac sympathetic activity was buffered by a decrease in intrinsic heart rate in these animals. Moreover, the impairment in baroreflex function observed in the adulthood group subjected to CVS was shifted to an improvement in animals subjected to repeated exposure to this stressor during adolescence and adulthood. The RRS in the adolescence+adulthood group caused a sympathetically-mediated resting tachycardia, which was not observed in the adulthood group. Significance: Our findings suggest that enduring effects of adverse events during adolescence included a vulnerability to neuroendocrine changes and a resilience to autonomic and cardiovascular dysfunctions caused by the CVS. Furthermore, results of RRS indicated a vulnerability to cardiovascular and autonomic changes evoked by homotypic stressors.
Keywords: Baroreflex; HPA axis; Restraint; Sympathetic activity; Unpredictable stress; Vascular reactivity